Penguatan Ekonomi Orang Tua pada Keluarga Anak Jalanan (Studi Kasus: Sanggar Alang-Alang Surabaya) - Puji Sucia Sukmaningrum; Siti Inayatul Faizah (Institut Teknologi Sepuluh Nopember, 2019)
The aim of this study is to find out the strategy on how to strengthen theeconomy welfare of street children’s family in Surabaya. Children are the nextgeneration of the nation whose all their needs should be fulfilled. Surabayaas one of the largest cities in Indonesia has some issues relating to povertyand street children. The research employed qualitative research method andthe informants were the street children in Sanggar Alang-Alang Surabaya.The result of the research showed that the strategy that can be given to parentsof the street children is the construction of the family workforce throughcreative economy programme, protection from discrimination against theirwork, provision of services, and creating productive business for poorfamilies.